C-reactive protein (CRP) recognizes uric acid crystals and recruits proteases C1 and MASP1. - Alberts, Anika; Klingberg, Annika; Wessig, Anne Kathrin; Combes, Christele; Witte, Torsten; Brand, Korbinian; Pich, Andreas; Neumann, Konstantin (Scientific Reports, 2020)
Gout is caused by crystallization of uric acid in the form of monosodium urate (MSU) crystals, which induce a sterile inflammatory response that is hardly distinguishable from microbe-induced inflammatory responses. It is unclear, if MSU crystals (like microbes) are recognized by specific pattern recognition receptors. To identify possible soluble pattern recognition molecules for MSU crystals, we purified MSU-binding proteins from human body fluids. We identified C-reactive protein (CRP) as a major MSU-binding protein. Binding of CRP was strong enough to specifically deplete CRP from human serum. We found that CRP was required for fixation of complement components C1q, C1r, C1s and MASP1. Thus, we have identified a pattern recognition molecule for MSU crystals that links to the activation of complement. Notably, CRP does not show an even binding to the complete surface of the crystals. It rather binds to edges or distinct faces of the crystals.
EVALuna2:424193